The Leadership of School Administrators Based on the Three Papanika Dhamma Principles Affecting Academic Administration under the Jurisdiction of the Nakhon Pathom Secondary Educational Service Area Office - Charoensaktanakul, Tharnun; Phravuddhanavajiramedhi, Phravuddhanavajiramedhi (Journal of Dhamma for Life, 2025)
The purposes of this research were: 1) to study the leadership of school administrators based on the three principles of Papanika Dhamma under the Secondary Educational Service Area Office, Nakhon Pathom, 2) to examine the academic administration of schools under the Secondary Educational Service Area Office, Nakhon Pathom and, 3) to study the leadership of school administrators based on the three principles of Papanika Dhamma and its impact on the academic administration of schools under the Secondary Educational Service Area Office, Nakhon Pathom. The sample group consisted of 58 school administrators and 259 teachers, totaling 317 respondents. The research instrument was a questionnaire, and data were analyzed using statistical software. The statistical methods applied included Frequency, Percentage, Arithmetic Mean, Standard Deviation, and hypothesis testing using Stepwise Multiple Regression Analysis. The results of this research were as follows: 1. The educational administrators' leadership based on the three principles of Papanika Dhamma under the Secondary Educational Service Area Office, Nakhon Pathom in overall was at the highest level. When considering each aspect individually, all are also at the highest level. In descending order, the leadership aspects are ranked as follows: Chakkhuma (visionary leadership), Nissayasampanno (collaborative leadership), and Vidhuro (expertise-driven leadership), respectively. 2. The academic administration under the Secondary Educational Service Area Office, Nakhon Pathom in overall was at the highest level. The aspects ranked from highest to lowest were as follows: creating a learning-supportive atmosphere and culture, developing students' potential, setting directions for change, supervision and evaluation of teaching performance, enhancing teachers' professional development and, curriculum instructional management, respectively. 3. The leadership of school administrators based on the three principles of Papanika Dhamma impact on academic administration under the Secondary Educational Service Area Office, Nakhon Pathom was statistically significant at the .05 level. The leadership aspects, ranked by importance, were Chakkhuma Leadership and Vidhuro Leadership. The multiple correlation coefficient (Multiple R) was .941, with these variables collectively predicting 88.6% (R² = .886) of the academic administration under the Secondary Educational Service Area Office, Nakhon Pathom. Forecast equations in raw score form y ̂tot = .085 + .040 (X2) + .046 (X1) (R2 = .886) Forecast equations in standard score form z ̂y = .721 (zx1) + .234 (zx2) (R2 = .886)